A Study on Rain Water Harvesting and Comparative Cost Analysis with Withdrawal of Underground Water around Gazipur City - Ashraful, AM; Islam, MM (Journal of Environmental Science and Natural Resources, 2015)
Rain water harvesting is a technology used to supply water for domestic purposes in developing countries. During dry weather, dust and other pollutants accumulate on the roof surface and are washed off at the beginning of the next rain. The initial contaminated volume of water flowing from a roof after a rain storm is known as the first flush and research has shown that diverting it from the main supply can improve the quality of stored water. An integrated planning for Rooftop Rain Water Harvesting system for different institutes in the premises an educational complex is done. The main objectives of the study are to estimate the roof top rain water harvesting potential and comparative cost analysis with withdrawal underground water. J. Environ. Sci. & Natural Resources, 8(1): 91-94 2015